Patologia do transplante renal: achados morfológicos principais e como laudar as biópsias - Sementilli, Angelo (2008)
Renal transplant has reached remarkable and growing rates of success since its introduction; nowadays it is a widely used replacement therapy. Renal allograft biopsies are increasingly more frequent in the routine of pathology laboratories, whose histological findings are varied. This paper results from the expertise of the members of the Kidney Club of Sociedade Brasileira de Patologia, and presents a general overview of renal allograft pathology, focusing on the current Banff classification, its main categories and cases of difficult diagnosis.